Effectiveness of protective measures in family violence processes guarantee the right to integrity of victims in the Superior Court of Justice of Tacna, headquarters, 2017. - Mejía Rodríguez, Ada Paola (2019)
The research carried out is of a social legal nature, of a descriptive-exploratory and dogmatic-juridical nature. Anonymous questionnaires (17 multiple choice and dichotomous questions) were applied to 341 participants, including trial lawyers in family violence, public defenders, magistrates and family court clerks, lawyers for the Women's Emergency Center (Tacna) and family prosecutors (holders and deputies). Likewise, a document analysis sheet was applied to collect data on 338 resolutions of hearings on protection measures in family violence processes. The investigation sought to determine the effectiveness of the protection measures granted to victims who denounce family violence before family courts of the Superior Court of Justice of Tacna (CSJT). Based on the results of the survey conducted and the review and analysis of the judicial resolutions, it was concluded that the protection measures granted to the victims by the magistrates of the four Family Courts of the CSJT are effective since guarantee the right to the integrity of the victims. Likewise, although the law itself expressly states that the National Police of Peru is the entity responsible for executing the protective measures ordered by the corresponding family court, most of the respondents consider that there is effective supervision of compliance with the measures of protection, this means that there is periodic follow-up of said measures granted in favor of the victim. On the other hand, the perception of the surveyed justice operators is that Law 30364 and non-regulation of conciliation is more effective than Law 26260, since Law 30364 guarantees the victim's right to integrity, generates more trust in justice and judges and projects it as a more severe measure to society.